Was ist Strafverteidigung? Eine Praxiseinführung (2.Auflage) - Bernard, Stephan (sui generis Verlag, 2021)
Few professions elicit such ambivalent feelings as criminal defense: If criminal defense lawyers win an innocent man an acquittal, they are admired. If, on the other hand, the criminal defense stands up for the rights of a felon, the recurring question is certainly how to defend him. Until now, there has been no introduction to the practice and craft of criminal defense in Switzerland. The book thus closes a central gap. It is not primarily aimed at experienced professionals, but also and especially at newcomers to the profession, students and an interested broad public. Stephan Bernard's vivid explanations are based on his earlier publications about criminal defense in professional and popular media. However, they are based at least as much on his personal knowledge and experience from over 15 years of broad criminal defense practice.